Stimulator of Interferon Genes-Associated Vasculopathy With Onset in Infancy: A Systematic Review of Case Reports - Dai, YunFan; Liu, XiuYun; Zhao, ZhiPeng; He, JianXin; Yin, QingQin (Frontiers in Pediatrics, 2020)
Objective: To summarize and analyze the manifestations of stimulator of interferon genes (STING)-associated vasculopathy with onset in infancy (SAVI). Methods: A systematic literature review was performed including cases from January 1, 2014, to February 1, 2020, using PubMed, OVID, CNKI, and WanFang. This included all the literature containing comparatively complete clinical data. Statistical analysis was performed using SPSS 20.0 to analyze the difference in age of onset, severity of skin lesions, and respiratory symptoms between SAVI patients with p.N154S and p.V155M mutations. Results: A total of 25 papers were included reporting on 51 individuals, of whom 17 had familiar inheritance of their mutation. Patients included 27 males and 24 females, and 8 fatal cases were observed. A total of 10 mutation sites have been reported in the STING gene, with p.V155M being the most prevalent. We identified SAVI as an early-onset disease with a median age of onset of 3 months after birth. Skin lesions were the most common symptoms of SAVI, found in 94.1% (48/51) of patients, while 76% (19/25) who had undergone a skin biopsy showed vasculopathy. Involvement of the lungs was identified in 68.6% (35/51) of patients, while only 22.2% (4/18) who had undergone a lung biopsy showed vasculopathy. Of 20 patients, 19 had increased immunoglobulin, mainly IgG. Furthermore, 45.1% (23/51) of patients had a positive low titer or were transiently positive for antinuclear antibodies. Of the 18 patients treated with JAK inhibitors, 6 relapsed and 2 died of acute respiratory failure caused by viral infection. Patients with p.N154S mutation had an earlier disease onset (p = 0.002) and more severe skin lesions (p < 0.001) than those patients with p.V155M mutation. Conclusion: SAVI is an early-onset disease accompanied by skin and lung lesions whose clinical presentation varies among patients with different genotypes. Therapeutic effects of JAK inhibitors are unsatisfactory.